2023
DOI: 10.1002/pan3.10564
|View full text |Cite
|
Sign up to set email alerts
|

The more the merrier? Perceived forest biodiversity promotes short‐term mental health and well‐being—A multicentre study

Kevin Rozario,
Rachel Rui Ying Oh,
Melissa Marselle
et al.

Abstract: Forests can foster mental health and well‐being. Yet, the contribution of forest biodiversity remains unclear, and experimental research is needed to unravel pathways of biodiversity–health linkages. Here, we assess the role of tree species richness, both actual and perceived, and how stress reduction and attention restoration can serve as potential mediating pathways to achieve positive mental health and well‐being outcomes. We conducted an experimental, multicentric field study in three peri‐urban forests i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 116 publications
0
9
1
Order By: Relevance
“…The accuracy of people's diversity estimations, however, might be influenced by whether they rate an environment's diversity alone, or in comparison to other environments. Of the studies that identified discrepancies between perceived and actual diversity, two studies used cross-sectional measurements (Dallimer et al, 2012;Phillips et al, 2021), while in Rozario et al (2024) participants were assigned to one environment only. In the present study, however, several forest environments were rated against each other, which enabled participants to directly compare diversity levels.…”
Section: Association Between Perceived and Actual Diversitymentioning
confidence: 99%
See 4 more Smart Citations
“…The accuracy of people's diversity estimations, however, might be influenced by whether they rate an environment's diversity alone, or in comparison to other environments. Of the studies that identified discrepancies between perceived and actual diversity, two studies used cross-sectional measurements (Dallimer et al, 2012;Phillips et al, 2021), while in Rozario et al (2024) participants were assigned to one environment only. In the present study, however, several forest environments were rated against each other, which enabled participants to directly compare diversity levels.…”
Section: Association Between Perceived and Actual Diversitymentioning
confidence: 99%
“…Studies have also juxtaposed the associations of measured and perceived biodiversity with mental well-being. In these cases, perceived biodiversity was found to have a stronger effect on mental well-being than measured biodiversity (Cameron et al, 2020;Dallimer et al, 2012;Farris et al, 2024;Rozario et al, 2024;Schebella et al, 2019;Zumhof, 2019). Indeed, Rozario et al (2024), Farris et al (2024 and Zumhof (2019) only found significant mental wellbeing effects for perceived biodiversity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations